Policy Target Populations and Public Participation in Agency Decision Making. Issue 2 (15th March 2018) - Neshkova, Milena I.; Guo, Hai (David)
ABSTRACT: Why are some government agencies more open to public input than others? Although many agree about the normative desirability of involving citizens in administrative decision making, there is significant variation across agencies in the extent of public participation. This article investigates the conditions under which public managers solicit greater public participation. We argue that, in addition to normative rationales, participation also serves instrumental considerations related to agency constituency. We draw on a rich body of literature examining participation in the policy process to develop empirically testable hypotheses about the patterns of participation in the administrative decision making of public agencies. Using data on the approaches to gathering citizen input in the budget process at four state departments—environmental protection, transportation, child protective services, and corrections—we find that the characteristics of target populations (namely, their political power and social construction) are strong predictors of an agency's openness to the public.